Tindak Tutur Asertif dalam Daftar Putar Pragmatik pada Kanal YouTube Kampus Virtual - Citra Resti Anggraini; Aisyah Salsha Febriana; Ela Indriyani; Sayka Absa Azzahra; Najma Sofi Yuliana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Hamlatus Sa’adah; Rofina Ayu Setia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Speech is the main means of conveying the purpose and purpose of the conversation, which is manifested through speech according to the context. This study aims to (1) identify assertive speech actions in the